CHINA’S MEDIATOR ROLE BETWEEN IRAN AND SAUDI ARABIA: IMPLICATIONS FOR THE UNITED STATES - Abdul Aziz; Dr. Zoonia Naseeb; Dr. Tahir Jamil (International Journal of Contemporary Issues in Social Sciences, 2024)
This research article examines and studies the outcome of the latest China broker deal between Iran and Saudi Arabia and the implications for the USA under this diplomatic development. The study inspects the historical context and the behavior of nations and their harsh policy among each other. By using the qualitative method to analyze how China as a mediator role toward regional power (Tehran and Riyadh) moreover, analyzing and scrutinizing the impending cooperation and regional security under the lens of balance of interest. further, study highlights the research questions such as which theory explains China’s role in Saudi Arabia and Iran? And what are the implications for the USA? And what are the interests of Beijing, Tehran, and Riyadh? Moreover, before this deal USA existed here with its influence of harsh policy created the gap which enabled China to play a card of ‘zero-enemy’ and good ‘friend’ policy to fill the gap. The two adversary states follow the framework of a win-win approach and then convert the balance of power strategy into the balance of interests under the China umbrella.